1967
DOI: 10.1139/m67-200
|View full text |Cite
|
Sign up to set email alerts
|

Marine Thiobacilli: I. Isolation and Distribution

Abstract: Bacterial colonies were isolated from Caribbean and Atlantic Ocean seawaters by the membrane filter technique and enrichment cultures in which thiosulfate was the only added source of energy. Although colonies were never abundant (0–275 per 100 ml), they have been recovered from the open ocean. The colonies were translucent to pale yellow on thiosulfate marine agar. The cells were Gram-negative motile rods (1–3 μ in length) requiring seawater for growth. The pH of the culture flasks dropped to 2.1 – 2.3 in som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

1971
1971
1993
1993

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…A widespread occurrence of sulphate-reducing bacteria would explain the paradoxical and ubiquitous presence of sulphide-utilizing strains of Thiobacillus (Tilton et al 1967a, b) and Thiobacillus-like bacteria (Tuttle & Jannasch 1972) in an otherwise oxygenated sea, that at the time would not be expected to be producing the reduced product hydrogen sulphide that is susceptible to oxidation by dissolved oxygen. The presence of bacteria in the MBC that could dark fix CO2 In reduced microparticulates, could also explain part of the dark fixation of CO2 attributed to nitrogen fixation in sedimenting particles (Karl et al 1988).…”
Section: Discussionmentioning
confidence: 99%
“…A widespread occurrence of sulphate-reducing bacteria would explain the paradoxical and ubiquitous presence of sulphide-utilizing strains of Thiobacillus (Tilton et al 1967a, b) and Thiobacillus-like bacteria (Tuttle & Jannasch 1972) in an otherwise oxygenated sea, that at the time would not be expected to be producing the reduced product hydrogen sulphide that is susceptible to oxidation by dissolved oxygen. The presence of bacteria in the MBC that could dark fix CO2 In reduced microparticulates, could also explain part of the dark fixation of CO2 attributed to nitrogen fixation in sedimenting particles (Karl et al 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Thiosulfate oxidation in organic media by some marine pseudomonads, with concomitant stimulation of growth, was reported by Tuttle et al (1974). They suggested that this may provide an ecological advantage for these organisms in environments such as the Black Sea (Sorokin, 1970), Cariaco Trench (Tuttle and Jannasch, 1973), and surface waters of oceans (Tilton et al, 1967) where thiosulfate is formed.…”
Section: Unidirectional Processesmentioning
confidence: 90%
“…the Black Sea and Cariaco Trench) lying beneath the euphotic zone. Thiobacilli could be found in inshore waters and sediments, but were rarely present in appreciable numbers in offshore waters and sediments or even in the Cariaco Trench (Tilton et al 1967).…”
mentioning
confidence: 94%
“…The importance of obligately anaerobic sulfate-reducing bacteria in marine sulfur turnover is generally accepted, but the aerobic portion of the marine microbial sulfur cycle in offshore water is not well understood. Studies on marine microbial sulfur oxidation (Tilton et al 1967;Adair and Gunderscn 1969) have focused mainly on the distribution of Thiobacillus sp. in the marine environment and were based on the assumptions that the microbial oxidation of reduced sulfur compounds in the sea is carried out by chemolithotrophic microorganisms similar to those found in terrestrial environments and that anaerobic photosynthetic sulfur-oxidizing bacteria are absent from aerobic offshore ocean waters or anoxic zones (e.g.…”
mentioning
confidence: 99%